Estudo dos casos dos rompimentos das barragens de Mariana e Brumadinho sob a ótica da (co)responsabilidade do Estado - Pereira, Kleyton (2023)
The business disasters in Mariana (2015) and Brumadinho (2019) revealed to the world the externalities of mining overexploitation and its most harmful effects on socio-biodiversity. In this context, two States of the Federation, dozens of Municipalities, and more than 1 million people were directly affected by the tailings mud from the dams of Samarco and Vale S/A. The acute damage caused by the mudflow was incessantly reported by the media, generating real social commotion. Currently, local populations continue to be subjected to the chronic and silent effects (which are being qualified and quantified) of the millions of cubic meters of tailings deposited in the Doce River and São Francisco River Basins. This devastation also constitutes an injury to the Federal Constitution, which in its article 225, establishes the right to an ecologically balanced environment as a diffuse right, essential to life, and imposes its protection as a duty of the State. Therefore, in view of the externalities of the cases under study, we investigate possible failures of the State in the protection of socio-biodiversity. To this end, the research questions: Did the State directly contribute to the occurrence of business disasters? Is the State (co)responsible for the collapse of the Samarco and Vale S/A tailings dams? To what extent could the State have prevented and/or mitigated its effects? In the search for these answers, we intend, from an emancipatory, prospective and preventive perspective of responsibilities, to contribute to the elaboration of theoretical legal models applicable to disaster rights. To this end, the contributions of the State in the social historical formation of industrialization since the 1930s were studied, and how this model influenced mining and the generation of a national dependence on foreign capital. Due to this cut, we opted for a dialectical approach with the typological method, using the basic theory of historical materialism, whose greatest exponent is Karl Marx. As a procedure, bibliographic research was carried out (especially those based on the Marxist Theory of Dependence), and the documentary analysis of judicial proceedings and technical reports of state control and inspection bodies. The research concluded, based on the quantification/qualification of damages and the causes of dam ruptures, the (in)existence of effective environmental licensing and inspection processes, and the safety and protection (or lack of safety and protection) of workers in mining, that the State was (co)responsible for the business disasters studied. Prospectively, it was concluded that the State has a duty to change the course of mining subjected to globalized capitalist overexploitation, under penalty of being held responsible in cases of future business disasters.